Voluntary wheel-running activities ameliorate depressive-like behaviors in mouse dry eye models - Nakano, Katsuya; Nakazawa, Hitomi; He, Qiang; Uwada, Junsuke; Kiyoi, Takeshi; Ishibashi, Takaharu; Masuoka, Takayoshi (Frontiers in Behavioral Neuroscience, 2022)
Recent clinical studies indicate that dry eye is closely associated with psychiatric disorders such as depression and anxiety. Here, we investigated whether two types of mouse dry eye models showed depressive-like behavior in forced swim and sucrose preference tests, and whether voluntary wheel-running helped ameliorate depressive states. To reproduce the dry eye models, the exorbital lacrimal glands (ELG) or exorbital and intraorbital lacrimal glands (ELG+ILG) were bilaterally excised from male C57BL/6J mice. Tear volume was persistently reduced in both models, but the ELG+ILG excision mice exhibited more severe corneal damage than the ELG excision mice. In the forced swim and sucrose preference tests, the gland excision mice showed longer immobility and shorter climbing times, and lower sucrose preference than sham-operated mice, respectively, which appeared earlier in the ELG+ILG excision mice. Wheel-running activities were significantly lower in the ELG+ILG excision mice, but not in the ELG excision mice. After short-period wheel-running, the longer immobility times and the shorter climbing times in the forced swim completely disappeared in both models. Our results suggest that dry eyes might directly cause a depressive disorder that depends on the severity and duration of the ocular surface damage, and that voluntary motor activity could help recovery from a depressive state induced by dry eye.